Ask Question
22 April, 02:53

Solve the equation by factoring. 3z^2+3z-6=0

0
Answers (1)
  1. 22 April, 03:14
    0
    Simplifying 3z2 + 3z + - 6 = 0 Reorder the terms: - 6 + 3z + 3z2 = 0 Solving - 6 + 3z + 3z2 = 0 Solving for variable 'z'. Factor out the Greatest Common Factor (GCF), '3'. 3 (-2 + z + z2) = 0 Factor a trinomial. 3 ((-2 + - 1z) (1 + - 1z)) = 0 Ignore the factor 3. Subproblem 1Set the factor ' (-2 + - 1z) ' equal to zero and attempt to solve: Simplifying - 2 + - 1z = 0 Solving - 2 + - 1z = 0 Move all terms containing z to the left, all other terms to the right. Add '2' to each side of the equation. - 2 + 2 + - 1z = 0 + 2 Combine like terms: - 2 + 2 = 0 0 + - 1z = 0 + 2 - 1z = 0 + 2 Combine like terms: 0 + 2 = 2 - 1z = 2 Divide each side by '-1'. z = - 2 Simplifying z = - 2 Subproblem 2Set the factor ' (1 + - 1z) ' equal to zero and attempt to solve: Simplifying 1 + - 1z = 0 Solving 1 + - 1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + - 1 + - 1z = 0 + - 1 Combine like terms: 1 + - 1 = 0 0 + - 1z = 0 + - 1 - 1z = 0 + - 1 Combine like terms: 0 + - 1 = - 1 - 1z = - 1 Divide each side by '-1'. z = 1 Simplifying z = 1Solutionz = {-2, 1}
Know the Answer?